2020
DOI: 10.5606/tgkdc.dergisi.2020.18387
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after cardiac surgery and preoperative vitamin D levels: A systematic review and meta-analysis

Abstract: Kalp cerrahisi sonrasında atriyal fibrilasyon ve ameliyat öncesi D vitamini düzeyleri: Sistematik derleme ve meta-analiz ÖZ Amaç: Bu meta-analizde, kalp cerrahisi sonrasında atriyal fibrilasyon gelişimi ve ameliyat öncesi D vitamini düzeyleri arasındaki muhtemel ilişki araştırıldı. Ça lış ma pla nı: Tarih sınırlaması olmaksızın PubMed, ScienceDirect ve Ovid elektronik veri tabanlarında literatür taraması yapıldı. Ameliyat öncesi D vitamini düzeylerinin ve ameliyat sonrası atriyal fibrilasyonun kaydedildiği İng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…One of the most important mechanisms is activation of the renin–angiotensin–aldosterone system. A meta-analysis conducted by Öztürk et al ( 55 ) found a significant relationship between the preoperative level of VitD and AF after cardiac surgery ( p < 0.05). Those results were consistent with those of our study, but pooled results had great heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important mechanisms is activation of the renin–angiotensin–aldosterone system. A meta-analysis conducted by Öztürk et al ( 55 ) found a significant relationship between the preoperative level of VitD and AF after cardiac surgery ( p < 0.05). Those results were consistent with those of our study, but pooled results had great heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 1, 25(OH) 2 D has exhibited an inhibitory effect on the renin‐angiotensin system, while vitamin D deficiency may activate the aforementioned system 27,28 . Several systematic reviews and meta‐analyses have concluded that vitamin D deficiency increases the risk of AF and POAF 29,30 . Furthermore, a dose–response meta‐analysis demonstrated that increasing vitamin D levels reduces the incidence of AF and POAF 31 .…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Several systematic reviews and meta-analyses have concluded that vitamin D deficiency increases the risk of AF and POAF. 29,30 Furthermore, a dose-response meta-analysis demonstrated that increasing vitamin D levels reduces the incidence of AF and POAF. 31 Interestingly, several epidemiological studies have demonstrated a higher prevalence of AF in winter, which may imply the role of vitamin D. 32,33 Furthermore, the level of vitamin D after CABG, among POAF group was less than those without this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although two meta-analyses 15,27 did not found a significant link, a meta-analysis with more subjects found vitamin D deficiency to be associated with atrial fibrillation. 18 Two systematic reviews and meta-analyses 28,29 were published addressing the same question. Neither of the studies did pay attention to the timing of vitamin D measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews and meta-analyses 28 , 29 were published addressing the same question. Neither of the studies did pay attention to the timing of vitamin D measurement.…”
Section: Discussionmentioning
confidence: 99%